Sewage sludge effects on soil biological parameters and on soybean nodulation and yield - Souza, Carla Albuquerque de; Reis Junior, Fabio Bueno dos; Mendes, Iêda de Carvalho; Lemainski, Jorge; Silva, José Eurípedes da (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this study was to evaluate the effects of applying sewage sludge produced by the Companhia de Saneamento Ambiental do Distrito Federal (Caesb) on the nodulation and yield of soybean and on the biological parameters of a Cerrado Oxisol. The experiment was done for two consecutive years in a completely randomized block design with three replicates and nine treatments – one control, four dosages of sewage sludge and four dosages of mineral fertilizer – applied only in the first year of the experiment. Soybean nodulation, grain yield, soil microbial biomass carbon, readily mineralizable carbon and activity of the beta-glucosidase, acid phosphatase and arylsulphatase enzymes were evaluated. In both years, the grain yield was lower than that of the mineral fertilizer only at the sewage sludge dose of 1.5 Mg ha-1. The application of sewage sludge in the first year of the crop does not affect soybean nodulation, and the application of up to 6 Mg ha-1 of sewage sludge had no effect on microbial biomass carbon, readily mineralizable carbon and on the activity of the beta-glucosidase, arylsulphatase and acid phosphatase soil enzymes in the two-year period.